2011
DOI: 10.1039/c0cp01794a
|View full text |Cite
|
Sign up to set email alerts
|

Product pair correlation in CH3OH photodissociation at 157 nm: the OH + CH3channel

Abstract: The OH + CH 3 product channel for the photodissociation of CH 3 OH at 157 nm was investigated using the velocity map imaging technique with the detection of CH 3 radical products via (2+1) resonance-enhanced multiphoton ionization (REMPI). Images were measured for the CH 3 formed in the ground and excited states (v 2 = 0, 1, 2, and 3) of the umbrella vibrational mode and correlated OH vibrational state distributions were also determined. We find that the vibrational distribution of the OH fragment in the OH + … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…32,33 Analysis of the fragment kinetic energy distributions for the O-H and C-O dissociation channels revealed that most of the available energy is channeled into translational kinetic energy, which also supports the possible mechanism of prompt fragmentation on the S 1 PES, which connects asymptotically to the CH 3 O + H and CH 3 + OH thermodynamic limits. 32,33,[35][36][37] In the valence isoelectronic system CH 3 SH, the S 1 and S 2 surfaces were previously explored by neutral fragment velocity map imaging 38 and ab initio theory. 8,39,40 In CH 3 SH, a conical intersection between the S 2 and S 1 PESs, involving C-S bond stretch and S-H motion, enables dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 Analysis of the fragment kinetic energy distributions for the O-H and C-O dissociation channels revealed that most of the available energy is channeled into translational kinetic energy, which also supports the possible mechanism of prompt fragmentation on the S 1 PES, which connects asymptotically to the CH 3 O + H and CH 3 + OH thermodynamic limits. 32,33,[35][36][37] In the valence isoelectronic system CH 3 SH, the S 1 and S 2 surfaces were previously explored by neutral fragment velocity map imaging 38 and ab initio theory. 8,39,40 In CH 3 SH, a conical intersection between the S 2 and S 1 PESs, involving C-S bond stretch and S-H motion, enables dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…This shows that the vibrational excitation of the correlated SH product is slightly anti-correlated to the CH 3 umbrella vibrational excitation, which is different from our previous work on CH 3 OH. 32 The OH distribution of CH 3 OH photodissociation at 157 nm on its second singlet excited state (2 1 A 0 0 ) is clearly anti-correlated to the CH 3 umbrella vibration excitation.…”
mentioning
confidence: 99%
“…Current molecular beam and laser techniques, in particular the fast-developing velocity map imaging method, make possible the measurement of the distribution of the translational energy between photodissociation products with an impressive accuracy, even for polyatomic reactions which are thus more and more studied. [1][2][3][4][5] Theoretical models are hence necessary to accurately predict product state populations 6 from which the translational energy distribution is straightforwardly deduced. 7 These models can then be used to analyse the reaction mechanism and find the key factors controlling the process.…”
Section: Introductionmentioning
confidence: 99%